2018
DOI: 10.3390/su10030797
|View full text |Cite
|
Sign up to set email alerts
|

New Zealand Winegrowers Attitudes and Behaviours towards Wine Tourism and Sustainable Winegrowing

Abstract: There are significant economic, environmental, social, and marketing issues that exist from the supply-side perspective in response to sustainability. This study examines New Zealand winegrowers in terms of their attitudes and behaviours towards wine tourism and sustainable wine production. A national survey was conducted at the end of 2015, which was the fourth such survey to be undertaken as part of a longitudinal study of wine tourism in New Zealand. This survey drew on issues of wine and biosecurity, clima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
91
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(100 citation statements)
references
References 90 publications
(175 reference statements)
5
91
0
4
Order By: Relevance
“…Although social marketing has tended to focus more on behavioural interventions in relation to climate change, commercial marketing has concentrated more on corporate marketing strategies (Božac & Tanković, ), and the commercial and consumer barriers to the adoption of new technologies, labelling or branding as part of adaptation and mitigation measures (Bocken, ; Ekelund & Spendrup, ; Finke, Gilchrist, & Mouzas, ; Fischer et al, ; Johnson, ; Koch, Sørensen, & Wildner, ; Radonjič, ). Sectors in which the role of commercial marketing has been examined include biofuel (Saravanan, Mathimani, Deviram, Rajendran, & Pugazhendhi, ), personal cars (Caperello & Kurani, ; Garland, Huising, & Struben, ; Saleem, Eagle, & Low, ), winegrowing (Baird, Hall, & Castka, ; Vink, Deloire, Bonnardot, & Ewert, ), property and real estate (Aune, ), and travel and tourism (Barr & Prillwitz, ; Cristobal‐Fransi, Daries, Serra‐Cantallops, Ramón‐Cardona, & Zorzano, ; Gössling, Scott, & Hall, ; Hall, ; Hoogendoorn & Fitchett, ; Scott, Steiger, Rutty, Pons, & Johnson, ; Tervo‐Kankare, Hall, & Saarinen, ).…”
Section: Research Themesmentioning
confidence: 99%
“…Although social marketing has tended to focus more on behavioural interventions in relation to climate change, commercial marketing has concentrated more on corporate marketing strategies (Božac & Tanković, ), and the commercial and consumer barriers to the adoption of new technologies, labelling or branding as part of adaptation and mitigation measures (Bocken, ; Ekelund & Spendrup, ; Finke, Gilchrist, & Mouzas, ; Fischer et al, ; Johnson, ; Koch, Sørensen, & Wildner, ; Radonjič, ). Sectors in which the role of commercial marketing has been examined include biofuel (Saravanan, Mathimani, Deviram, Rajendran, & Pugazhendhi, ), personal cars (Caperello & Kurani, ; Garland, Huising, & Struben, ; Saleem, Eagle, & Low, ), winegrowing (Baird, Hall, & Castka, ; Vink, Deloire, Bonnardot, & Ewert, ), property and real estate (Aune, ), and travel and tourism (Barr & Prillwitz, ; Cristobal‐Fransi, Daries, Serra‐Cantallops, Ramón‐Cardona, & Zorzano, ; Gössling, Scott, & Hall, ; Hall, ; Hoogendoorn & Fitchett, ; Scott, Steiger, Rutty, Pons, & Johnson, ; Tervo‐Kankare, Hall, & Saarinen, ).…”
Section: Research Themesmentioning
confidence: 99%
“…In this sense, the image of a sustainable product with a small carbon footprint can be appreciated. The perception of sustainability in other countries has been addressed [31,32], but this work is especially focused on the use of renewable energy. In another direction, there are studies [33] which question whether innovations in wine are well received by consumers, as they can break from the traditional product image associated with wines from the old world.…”
Section: From Attitudes To Innovations In the Wine Sectormentioning
confidence: 99%
“…Regarding the wine sector, some studies [31,32,34,41] have shown limited adoption of environmental innovations, although with some regional differences. This coincides with the low adoption of renewable energy observed by the present study.…”
mentioning
confidence: 99%
“…Spielmann (2017) found diversity in environmental sustainability attitudes and practices in the French wine industry that are causally related to business size and engagement in direct investment in foreign markets. Baird et al (2018) found that New Zealand winegrowers faced significant economic, environmental, social, and marketing challenges from the supply-side perspective in response to sustainability. They indicated substantial concerns with the perceived value provided by sustainable winegrowing practices at both the firm and governing-body levels.…”
Section: Introductionmentioning
confidence: 99%